FAKTOR PENYEBAB KESENJANGAN GENDER PADA PEREMPUAN DALAM MENDAPATKAN PENDIDIKAN DI KABUPATEN MALAKA - Frederika Yolanda Bria (Prosiding Ilmu Pendidikan dan Keguruan, 2023)
The purpose of this study was to describe (1) the gender gap in women's access to education in Umalor Village, and (2) to describe the factors that cause gender gaps in women's access to education in Umalor Village. The type of this research was descriptive qualitative, and data collection methods used observation, interviews, and documentation. The research subjects were village heads, parents and children who did not continue their education to a higher level. The analysis technique of the data used data collection, data reduction, data presentation, and drawing conclusions. The results of this study are (1) women's education is secondary (subordination), compared to men; (2) women's education is marginalised and given less attention (marginalization) because women only take care of domestic needs; (3) there is labelling (stereotypes) given to women as creatures who are weak and unable to lead themselves; and (4) women's workload is more than men's work, namely women who have to work in the house and outside the house. Meanwhile, the factors that cause gender gaps in women's access to education include (1) cultural tradition factors that prohibit and limit women's rights and obligations to access education, (2) patrilineal cultural factors that consider men to be more capable than women, and (3) the economic limitation factor so that boys are sent to school earlier than girls.